PENGARUH BRAIN GYM TERHADAP KEMAMPUAN MEMBACA ANAK TUNAGRAHITA - I Putu Septiawan (Coping: Community of Publishing in Nursing, 2015)
Mental retardation children are children that have many disabilities such as learning disability especially in reading, writing and calculating. Reading is complex activity that include physic and mental, that also need more brain function than any other activities. High concentration is needed when you read so all the information that you get when reading can be transmitted, processed and stored inside the brain. Children with mental retardation have difficulty processing and remembering information that makes them harder to learning something especially reading. Learning process especially reading will be best if both lobes of the brain could work optimally. One of activity that can use all part of the brain is Brain Gym. The aim of this research was to identify effect of Brain Gym on reading ability among fifth grade mental retardation children at Sekolah Dasar Luar Biasa Negeri in Bali Province. This research was conduct for 1 month at Sekolah Dasar Luar Biasa Negeri C Denpasar and Sekolah Dasar Luar Biasa Negeri Gianyar. The sample in this research consists of 20 children with mental retardation in fifth grade. This research used Quasi Experimental with Nonequivalent Control Group design. In measuring the children reading ability the researcher used reading test from EGRA. Outcome was processed by Saphiro Wilk test for normality test and then used parametric test Independent t Test. The result revealed significant difference of reading ability between experimental group and control group with sig. (2-tailed) 0,000 (p value < 0,05) which means null hypothesis (Ho) was rejected, there was a significant impact of Brain Gym for reading ability among fifth grade mental retardation children at Sekolah Dasar Luar Biasa Negeri in Bali Province.